The Catch of Little Tuna (Euthynnus sp.) in Relation to Thermal Front in the Makassar Strait - Khoir, Miftahul; Safruddin, Safruddin (Hasanuddin University, 2023)
The Makassar Strait waters area is a potential area for the utilization of marine fishery resources in Indonesia especially for large pelagic fisheries because it is one of the migration trajectories of little tuna (Euthynnus sp.). In order to optimally utilize tuna resources, remote sensing technology based on oceanographic satellite imagery can be relied upon to facilitate identification, prediction, and spatial and temporal mapping of potential fishing areas. This study aims to study the phenomenon of oceanography (thermal front) as an indicator of potential for little tuna fishing areas in the Makassar Strait. Primary data was obtained through in-situ data collection (direct observation in the field by following fishing operations using the purse seine, while secondary data consisting of oceanographic data such as sea surface temperature and sea surface chlorophyll-a concentrations sourced from satellite imagery data (Aqua satellite with MODIS sensor). The distribution of the thermal front was analyzed using ArcGIS 10.4 software to determine the relationship between little tuna fishing productivity and the oceanographic phenomenon. Based on the analysis results, total of 61 positions for little tuna fishing using a purse seine, five (5) fishing positions were in the thermal front area, where the catch of little tuna is higher than the average catch outside the area. These results indicate that the thermal front can be used as an indicator of potential for little tuna fishing areas in the Makassar Strait.